The Effect of Profitability, Liquidity, Leverage, and Firm Size on Firm Value in The Automotive and Component Subsector Listed on The Indonesia Stock Exchange For The Period 2015–2024 - Mutiara Rachma Putri; Mansyur Hirdinis (International Humanities and Applied Science Journal, 2026)
The purpose of this research is to find out how profitability, liquidity, leverage and firm value affect firm value. The correlations among the variables were examined using a causal study design and a quantitative technique. Eighteen firms, all involved in the automotive and component industries, that were listed on the IDX between 2015 and 2024 make up the study's population. Five firms selected through purposive sampling consistently published full financial statements over the course of the ten-year study. A total of 50 observations were included in the research and evaluated using EViews 13. The primary technique for analysis was panel data regression. Firm value is positively and significantly impacted by profitability and leverage, according to the data. Firm value is significantly and negatively impacted by firm size. On the other hand, liquidity doesn't seem to have much of an impact on company valuation.  Keywords: profitability, liquidity, leverage, firm size, firm value